Effects of Rotor Bar and End-Ring Faults Over the Signals of a Position Estimation Strategy for Induction Motors - Bossio, Guillermo Rubén (2005)
The effect of rotor faults, such as broken bars and end-rings, over the signals of a position estimation strategy for induction motor drives is analyzed using a multiple coupled circuit model. The objective of this analysis is to establish the possibility of using the estimation strategy signals for fault diagnosis in variable-speed electric drives. This strategy is based on the effect produced by inductance variation on the zero-sequence voltage, when exciting the motor with a predefined inverter switching pattern. Experimental results illustrate the feasibility of the proposal.